POLITICAL AND LEGAL ASPECTS OF STATE-CHURCH RELATIONS IN THE UNITED STATES OF AMERICA - Стеблак, Д. М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
The political and legal aspects of forming a model of state-church relations in the USA are reviewed. The legal and regulatory framework regulating relations between the state and the church in the USA is described. The model of relations between the state and the church in the USA in different spheres is analyzed. The features of the American model of state-church relations are investigated, the causes and factors of religious tolerance in the country are determined.The views of the founding fathers of the American Constitution - T. Jefferson and J. Madison, which formed the basis of the state's attitude to religious issues, are analyzed. The role of the United States Declaration of Independence signed in 1776 in America, approved by the Second Continental Congress of the North American Colonies in the United Kingdom, of the Charter of Virginia Statute of Religious Freedom, the «Virginia Statute on Religious Freedom» adopted by the General Assembly of the State in 1786, the US Constitution, which was adopted on September 17, 1787, which came into force in 1789 and ratified in all thirteen states  is described.. The role of the First Amendment, one of the ten ones, which formed the Bill of Rights (Bill of Rights, 1791), was explored. USA is one of the most religious countries in the world. The US population regularly visits the churches.In every elections of every next official religion shows its importance. Almost all the most important events, speeches of politicians, oaths of senior civil servants begin with the words of the Bible.